The Influence of Technology in English Learning at SMA Muhammadiyah 2 Sidoarjo: Students' Voices - Yuli Astutik; Nisrina Mutia Oktavira; Britania Agnelisa Dennysa Putri; Nilam Lailiyatul Qomariyah; Florentine Ananda RatnaNegara; Hilwa Firza Bahri; Khoirul Umam; Retno Nurlilawati; Nisrin Adelyna Darayani (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2024)
This study aims to assess the influence of digital tools, specifically Zoom and Quizizz, on students' engagement, motivation, and interaction within English language learning at SMA Muhammadiyah 2 Sidoarjo. Using a quantitative descriptive survey method, data were collected from 66 students in grades XI-9 and XI-11 through a Likert-scale questionnaire. Findings reveal that students generally view these tools positively, as they facilitate interactive and flexible learning. Zoom is valued for real-time discussions, supporting language practice, while Quizizz enhances assessment processes by making quizzes interactive and providing instant feedback, which improves information retention and motivation. The study underscores the dual role of technology as both a facilitator and a barrier, depending on resource availability. Implications highlight the need for strategic investments in educational technology infrastructure and digital literacy training to maximize the potential of digital tools in English learning.